AN ANALYSIS HYPERBOLE IN MY SUNSHINE NOVEL BY CATHERINE ANDERSON - IKA TRISNANTASARI (Fakultas Sastra Universitas Gresik, 2016)
This research intends to find figurative language in the novel My Sunshine, especially hyperbole, one of the factors the book being the best seller romance novel internationally.The researcher used qualitative method. The researcher analyzed original novel and compare to figurative language. Figurative languages, used as a tool for the author to bring the more realistic situation, bring the reader to understand and sympathies to the characters in the novel they read, then the researcher find out and analysis meaning hyperbole in My Sunshine Novel by Catherine Anderson.Catherine Anderson writer bring the realistic and relatable character in this novel, through the style writing is conveyed well, the reader must know the character and they are all so well develop and portrayed. And the reader really get dig deep into the main characterÃ¢â‚¬â„¢s emotions, hyperbole emphasizing the emotions felt whilst reading this novel, which is similarly beautiful and exaggeration. This function of hyperbole is researcher found influence with the quality the novel, so it can achieve the number of awards.Realizing the fact above, the researcher decided to do as good as possible in the study of Ã¢â‚¬Å“HyperboleÃ¢â‚¬Â. By having careful analysis of the figurative language of the hyperbole as they are so well emphasized by its author Catherine Anderson.Ã‚Â Key Words: Analysis, Hyperbole, Personification, Novel.